Quantifying the Effect of Water Deficit on Cotton Genotypes Using Agro-physiological and Biochemical Parameters. Issue 12 (2nd December 2021) - Chattha, Waqas Shafqat; Shakeel, Amir; Iqbal, Muhammad; Yaseen, Muhammad; Amin, Muhammad; Mahmood, Naeem
ABSTRACT: To investigate the water-deficit tolerance, 45 cotton genotypes were grown under normal irrigation and water-deficit conditions for 2 years. Genotype × treatment × year interaction was determined for seed cotton yield, number of bolls, boll weight, chlorophyll fluorescence, proline contents, and total soluble proteins. Apart from proline levels, all traits showed a reduction under water-deficit conditions. The mean percentage reduction in seed cotton yield due to water deﬁcit conditions was 52.83% and 42.19%, for number of bolls was 48.44% and 39.30%, for boll weight was reduced by 8.94% and 6.03% in 2013 and 2014 respectively. Reduction in chlorophyll fluorescence was 13.87% and 16.46% while soluble protein levels decreased by 25.57% and 21.09% during 2013 and 2014 respectively. For proline contents went up by 38.68% and 37.70% in 2013 and 2014 respectively. Relatively small changes in these parameters under water-deficit conditions were recorded for varieties FH-155, FH-207, FH-322, FH-329 IUB-13 and IUB-222 making these genotypes best suited for cultivation under water-deficit conditions. The positive correlation of seed cotton yield with proline contents and chlorophyll fluorescence under water-deficit condition indicates that these two traits can be considered to select cotton genotypes at early growth stages.